1997
DOI: 10.1177/036354659702500604
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Surgery for Lateral Tennis Elbow

Abstract: We undertook a retrospective analysis of 34 patients (35 elbows) who had prior failed surgical intervention for lateral tennis elbow. Revision surgeries were performed between 1979 and 1994. Each patient's non-operative and operative history was recorded before our salvage revision surgery. At revision surgery, findings included residual tendinosis of the extensor carpi radialis brevis tendon in 34 of 35 elbows. In 27 elbows, the pathologic changes in the extensor carpi radialis brevis tendon had not been prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 12 publications
0
32
0
1
Order By: Relevance
“…3 It was assumed simply that all pain represented failure to relieve the initial pain of lateral humeral epicondylitis or some other explanation was offered such as "anxiety neurosis in two patients," 1 "patient involved in litigation," 2 and "workers' compensation patients with disability determination still pending." 4 It is possible that a neuroma of the PCNF was the source of pain noted in a previous study in the 5 patients who failed to obtain relief from radial tunnel surgery in a population of patients who had had surgery previously for lateral humeral epicondylitis. 10 Patients were chosen for radial neurolysis by presurgical response to steroid plus lidocaine infiltration of the radial tunnel, which would have blocked pain signals from a neuroma of the PCNF.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…3 It was assumed simply that all pain represented failure to relieve the initial pain of lateral humeral epicondylitis or some other explanation was offered such as "anxiety neurosis in two patients," 1 "patient involved in litigation," 2 and "workers' compensation patients with disability determination still pending." 4 It is possible that a neuroma of the PCNF was the source of pain noted in a previous study in the 5 patients who failed to obtain relief from radial tunnel surgery in a population of patients who had had surgery previously for lateral humeral epicondylitis. 10 Patients were chosen for radial neurolysis by presurgical response to steroid plus lidocaine infiltration of the radial tunnel, which would have blocked pain signals from a neuroma of the PCNF.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge there is no mention of this nerve in the detailed descriptions of the surgical procedure for lateral humeral epicondylitis or radial tunnel surgery. [1][2][3][4][5][7][8][9] The best way to protect the PCNF from injury is to remember that its location places it at risk during surgery in this region and to identify the nerve immediately after making the skin incision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benazzo et al (1996) in a study on athletes undergoing surgical exploration of Achilles and patellar tendons, observed a return to full activity in 79% of the younger patients, where a minor degree of tendon degeneration was present. Mechanical load is regarded as the most important etiologic factor in disorders affecting human tendons (Khan et al, 1999;Movin, 2000) and important changes affect tendon tissue in pathologies such as lateral epicondylitis (Organ et al, 1997;Kraushaar and Nirschl, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Our study describes a typical group of patients, in the fourth or fifth decades of life, with long-standing symptoms not responding to nonoperative modalities of treatment [9,15,21,23].…”
Section: Discussionmentioning
confidence: 99%